Handmade tales : sustainable fashion through craft connections : a thesis submitted in partial fulfilment for the degree of Master of Design, Massey University, Wellington, New Zealand - Kapur, Harita (Massey University, 2016)
India is a country with an ancient history. The crafts of this country are diverse and are a reflection of the country’s cultural heritage. According to Dasra (2013), the craft industry provides millions of artisans with employment and is one of the largest small scale or cottage industries. For centuries, these craft communities have specialized in traditions that are specific to the regions and respective skills, which have been handed down from generations of artisans. Yet in recent years, as Wood (2011) notes, this sector faces a major threat as a result of growing preference for mass produced designs that are cheap and easy to afford. This has contributed to the steady decline of craft based products. This, alongside a lack of knowledge of new innovative ways to design, and decreasing demand for their products have left the craftspeople very vulnerable and has posed a big threat to their sustainable livelihoods. Integrating fashion design with artisan textiles can help regenerate the community and village culture while enhancing the value of products. This practice led research project offers a framework to meet the emerging challenges associated with ethical and environmental principles linked with fashion by incorporating sustainable processes used in traditional craft production. Importantly, it can also offer one strategy to support economic sustainability issues linked to the livelihood of craftspeople at the village level. The project develops an example of a sustainable fashion design process by drawing from the rich heritage of Indian crafts and focuses on developing a fashion collection that integrates artisan craft textiles into the design process. This reaches out to a market that is sensitive towards sustainability issues linked to artisan livelihood and fashion and values the handmade and organic as an alternative approach. This exploration of issues related to sustainability both for fashion design and craft is an attempt to uncover why developing a relationship between the two is significantly more relevant today than it ever has been.
Keywords: Harita Kapur; Fashion design; Textile fabrics; Handicraft; Dyes and dyeing; Sustainable design; India; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Art